PERAN MEDITASI DALAM PENYELESAIAN PROBLEM FISIK DAN MENTAL DI PERGURUAN SILAT CIPTA SEJATI SUMENEP - Maghfiri Rofiqi; Muhammad Alfan Sidik (Living Sufism: Journal of Sufism and Psychotherapy, 2024)
Silat is an Indonesian culture that teaches self-defense techniques and methods in solving problems. One of the solutions is by meditating. However, not all martial arts use meditation as problem solving. Most meditation is only used for personal gain. In contrast to the Cipta Sejati martial arts Sumenep, the meditation is not only used for individual interests but is used to treat others. This research aims to reveal two things: First, how the role of meditation of the Cipta Sejati martial arts Sumenep in solving physical and mental problems. Second, how the meditation process of the Cipta Sejati martial arts Sumenep in solving physical and mental problems. In order to facilitate this research, researchers used a qualitative research type, case study approach, interview, observation and documentation methods. Researchers rely on two theories, namely Robert Frager's takhalli, tahalli and tajalli theories for problem-solving methods with soul purification. Anand Krishna's theory, Sufi meditation to measure the meditation process of the Cipta Sejati martial arts Sumenep. This study concludes that the role of meditation in solving physical and mental problems is to restore awareness, self-cleaning from liver disease, habituation to good nature, unification with God, focusing on one point and to clean, organize, ogram and raise the chakra as a power center in healing. The process of solving problems with meditation, namely: Providing a safe place, purifying and cleaning oneself, providing a name or photo, request meditation, smile and cleansing meditation, energy fence meditation, reading treatment practices, patient's inner contact, cleansing dirty energy, channeling treatment energy, channeling the patient's energy fence and final request meditation.